PERANAN SISTEM INFORMASI AKUNTANSI PERSEDIAAN BAHAN BAKU DALAM MENUNJANG KELANCARAN PRODUKSI PADA PT. DASKO DAVITEK PERSADA - Aloina BR Purba; Malesa Anan (Worksheet : Jurnal Akuntansi, 2021)
Inventory of raw materials plays an important role for the company, because it isan element of company assets that have material value in a relatively large amountand value, as well as assets that are sensitive to time, decline in market prices,damage and excess costs caused by errors in handling. The formulation of theproblem in this study is whether the application of the accounting informationsystem for raw material inventory at pt. Dasko davitek persada has beenimplemented effectively and efficiently and how is the role of the accountinginformation system for inventory of appropriate raw materials so that it can supportthe smooth running of production at pt. Dasko davitek persada. Pt. Dasko davitekpersada has been implemented effectively and efficiently, as well as to determinethe role of the appropriate raw material inventory accounting information systemin supporting the smooth production process at pt. Dasko davitek persada.Keywords : Accounting Information System, Raw Material Inventory, Smoo